Effect of Diabetes Patient Care System Development Process, Huay Phueng Hospital, Kalasin Province - Uaichean , Phitoon; Suttipapar, Teerapat (Journal of Health Science of Thailand, 2021)
This research was research and development aimed to studied the health status of diabetes mellitus patients, guidelines for care and the process of developing DM care system Huay Phueng Hospital Kalasin Province. Conducted studies between September 2017 and October 2019, totaling 25 months of study. Sample size were 444 DM patients who come to services at Huay Phueng Hospital Kalasin Province. The tools used for collecting data were health log recording. Data were analyzed by frequency distribution, percentage, mean, standard deviation, logistic regression with adjust ODDs ratio, F–test by technique Repeated measurement and content analysis. The results showed that A1C of DM patients Huay Phueng Hospital Kalasin Province between 2017, 2018 and 2019 were significantly different at the level of 0.05 (p<0.01) with the lowest level of A1C in 2019.